Pengaruh Kepuasan Kerja, Komitmen Organisasional, dan Kompensasi terhadap Turnover Intention pada Karyawan Troy Company - Fatimah Hikmah; Hari Nurweni (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2022)
This study aims to determine there is an influence of job satisfaction, organization commitment, and compensation on turnover intention to the Troy Company employee. Independent variables in this study consists of job satisfaction, organization commitment, and compensation. As a dependent variable is turnover intention. This study used quantitative method, and using questionnaire to collect a data. This study was conducted in september 2022, at the Troy Company which is located in Yogyakarta. The population in this study is all the employees of the Troy Company, and the sample in this study is 40 employees. The sampling technique is using a census method. The data analyzed by the t-test, F-test (goodness of fit), and multiple linear regression using the SPSS 25.00 program. The results of this study show that: (1) Job satisfaction has a negative significant effect on the turnover, (2) Organization commitment has a negative significant effect on the turnover, (3) And compensation has a negative significant effect on the turnover of the Troy Company.